I am having trouble with this problem as I have just started doing logic. Is this the same as

P → Q
Prove: ¬P ∨ Q


  • 3
    Which text book are you using? An online proof checker and text book may be helpful as supplementary material: proofs.openlogicproject.org Commented Apr 23, 2019 at 1:08
  • 1
    Welcome to PSE. The answers hint at how to find a proof. But your question seems to be whether proving P → Q from ¬P ∨ Q is the same as proving ¬P ∨ Q from P → Q to which the answer is "No, this is not the same thing, though the proofs might look (structurally or otherwise) similar". Commented Apr 23, 2019 at 8:13
  • The two statements should have the same truth values. Would that analysis assist in showing equivalence? Commented Apr 23, 2019 at 23:09

3 Answers 3


In a natural deduction system (if that is what you are using) to prove a conditional, such as is P → Q, you must use a Conditional Proof.

This takes the form of assuming the antecedent (that is P) aiming to derive the consequent (that is Q) through valid inferences (also using the premises; that is ¬P ∨ Q). Then discharging the assumption allow the deduction of the conditional (that is P → Q).

Now to prove Q from an assumption of P and the premise of ¬P ∨ Q, either use Disjunctive Syllogism, or a Proof by Cases.


In this particular case, the two statements are equivalent: (¬P ∨ Q) ⊢ (P → Q) and (P → Q) ⊢ (¬P ∨ Q) are both provably true statements, so (¬P ∨ Q) ≡ (P → Q).

But in order to prove that equivalence, we need to prove both directions separately. To see why, consider the case where instead of (¬P ∨ Q) and (P → Q), we have these two statements:

  • P
  • P ∨ Q

We can trivially prove that (P ∨ Q) follows from P; this is more or less the definition of the addition rule. But P does not necessarily follow from (P ∨ Q), since (¬P ∧ Q) also satisfies that clause. We can prove it in one direction, but they are not equivalent statements.

  • The two statements are logically equivalent using the material implication rule. Draw out a truth table and see for yourself that the tables are 100 percent identical.
    – Logikal
    Commented Apr 23, 2019 at 23:45
  • @Logikal I know they are equivalent. I said they are equivalent. But the OP isn't asking if they're equivalent; they are asking if, having already proven A ⊢ B, you must still prove B ⊢ A in order to establish that an equivalence exists. The answer to that is "yes". The fact that this particular equivalence has already been proven doesn't change that.
    – Ray
    Commented Apr 24, 2019 at 1:24

If one uses a truth table generator one can show that (¬P ∨ Q) ↔ (P → Q). To see this, insert the following input into the Stanford Truth Table Tool: (~P or Q)<=>(P=>Q)

This shows that the two statements are equivalent.

However, the question asks one to prove P → Q given the premise ¬P ∨ Q. Here is how one might do this using a natural deduction proof checker:

enter image description here

See the links below for an explanation of the rules used by this proof.

The proof would not be the same if we wanted to prove ¬P ∨ Q given the premise P → Q. That proof would look like this:

enter image description here

Although the statements are equivalent based on a truth table generator, the proofs from one to the other may be different depending on which is the premise and which the conclusion.

Kevin Klement's JavaScript/PHP Fitch-style natural deduction proof editor and checker http://proofs.openlogicproject.org/

P. D. Magnus, Tim Button with additions by J. Robert Loftis remixed and revised by Aaron Thomas-Bolduc, Richard Zach, forallx Calgary Remix: An Introduction to Formal Logic, Winter 2018. http://forallx.openlogicproject.org/

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .